Comparing Turbulence Models for CFD Simulation of UAV Flight in a Wind Tunnel Experiments: Comparing turbulence models - Aljuhaishi, Saif; Al-Timimi, Yaseen K.; Wahab, Basim I. (Periodica Polytechnica Transportation Engineering, 2024)
Wind tunnel tests are costly and time-consuming, and the accuracy of the tests is limited by the size of the tunnel, to solve this problem, researchers use computational fluid dynamics (CFD) to conduct wind tunnel experiments using a computer because it is less timely and less costly. Computerized testing of drone's models using wind tunnel experiment simulation in computational fluid dynamic (CFD) software requires knowledge of the most suitable turbulence model for this drone. In this paper ANSYS fluent program has been used to test four most common turbulence models for use (Spalart-Allmaras, K-Epsilon, K-Omega and Reynolds stress) and laminar flow on the ScanEagle drone model (an aerial reconnaissance drone used in military and intelligence operations) and calculated their effect on aerodynamic parameters In terms of accuracy and time to solution, concluded that the best turbulence model in terms of balancing accuracy and the time taken for the calculation is K-Omega model.